Integrative multi-omics and biochemical validation reveal phenol-to-polyhydroxybutyrate conversion in a palm oil mill effluent microbiome - Sabri, Izzati; Sharuddin, Siti Suhailah; Mohd Yusoff, Mohd Zulkhairi; Nor Muhammad, Nor Azlan; Ho, Li Sim; Maeda, Toshinari; Ramli, Norhayati (Elsevier, 2026)
Phenol-degrading bacteria offer a green biotechnological route for phenol detoxification and bioplastic production through polyhydroxybutyrate (PHB) biosynthesis. However, the microbial mechanisms that link phenol degradation to PHB accumulation in palm oil mill effluent (POME) microbiomes remain poorly understood. This study provides an integrative understanding of microbial composition, active functional genes, metabolic pathways, and biochemical validation that collectively underpin phenol-to-PHB conversion. Microbial communities from POME biotreatment ponds were first analyzed using 16S rRNA amplicon sequencing, followed by metatranscriptomics profiling of the most promising community. Phenol degradation and PHB accumulation were validated in batch cultivations. Metatranscriptomics analysis of the POME microbiome from aerobic pond revealed that phenol degradation was primarily associated with the complete catechol degradation I ( meta -cleavage) pathway. Concurrent expressions of catechol ortho -cleavage and protocatechuate degradation pathways, enriched in distinct taxa, suggest partial functional specialization within the community. Notably, Cupriavidus , Pseudomonas , Bacillus , and Vibrio exhibited transcriptional potential to couple phenol degradation with PHB synthesis . This community completely degraded 0.3 g/L phenol within 24 h, producing 0.06 ± 0.012 g/L PHB. Transmission electron microscopy (TEM), Fourier-transform infrared (FTIR), and 1H Nuclear Magnetic Resonance (NMR) analyses confirmed the identity of the extracted polymer as PHB. The POME microbiome shows promise for integrated phenol remediation and bioplastic production, highlighting the broader value of leveraging waste-derived microbiomes for a circular bioeconomy.